Anti‐Tumorigenic Potential of a Novel Orlistat‐AICAR Combination in Prostate Cancer Cells. Issue 11 (23rd May 2017) - Wright, Clayton; Iyer, Anand Krishnan V.; Kaushik, Vivek; Azad, Neelam
ABSTRACT: Prostate cancer (PCa) is one of the leading causes of cancer‐related deaths in men worldwide. Fatty acid synthase (FASN) is reported to be overexpressed in several cancers including PCa, and this has led to clinical cancer treatments that utilize various FASN inhibitors such as the anti‐obesity drug, Orlistat. However, pharmacological limitations have impeded the progress in cancer treatments expected thus far with FASN inhibition. In this study, we investigated a novel therapeutic combination to enhance the toxic potential of Orlistat in three different PCa cell‐lines (DU145, PC3, and LNCaP). We show that Orlistat and 5‐Aminoimidazole‐4‐carboxamide ribonucleotide (AICAR) (AMP‐activated protein kinase [AMPK] activator) co‐treatment induces significant downregulation of two key fatty acid synthesis regulatory proteins (FASN, Sterol regulatory element‐binding protein 1 [SREBP‐1c]) as compared to control and Orlistat alone. Orlistat and AICAR co‐treatment induced a significant decrease in cell viability and proliferation, and a significant increase in apoptosis in all three PCa cell‐lines. Apoptosis induction was preceded by a marked increase in reactive oxygen species (ROS) production followed by G0/G1 cell cycle arrest and activation of pro‐apoptotic caspases. We also observed a significant decrease in migration potential and VEGF expression in Orlistat and AICAR co‐treated samples in all three PCa cell‐lines. Compound C (AMPK inhibitor) negatively affected some of the enhanced anti‐cancer effects observed with Orlistat treatment. We conclude that AICAR co‐treatment potentiates the anti‐proliferative effects of Orlistat at a low dose (100 µM), and this combination has the potential to be a viable and effective therapeutic option in PCa treatment. J. Cell. Biochem. 118: 3834–3845, 2017. © 2017 Wiley Periodicals, Inc. Abstract : The potentiation of Orlistat cytotoxicity using AICAR in PCa cells is proposed. Apoptosis is enhanced, and cell viability and proliferation is decreased. The mechanism depends on ROS production, caspase activation, and cell cycle arrest. This Orlistat‐AICAR combination therapy may provide a viable PCa treatment option.